Controlling shareholders and payout policy: Do founding families have a special "taste for dividends"? - Thomas Schmid; Markus Ampenberger; Christoph Kaserer; Ann-Kristin Achleitner (Verein für Socialpolitik, 2010)
Around the world (with the U.S. and U.K. as exceptions) concentrated ownership structures and controlling shareholders are predominant even among listed firms. We provide novel empirical evidence how such controlling shareholders, in particular founding families, affect payout policy decisions. Thereby, we use a unique panel dataset of 660 listed firms in the 1995 to 2006 period from Germany, an economy that is traditionally characterized by concentrated ownership structures and strong family capitalism. We find that family firms exhibit a higher propensity and level for both dividend payments and total payouts. This result is driven by family ownership rather than family management. Conflicts between the founding family and non-family controlling shareholders and tensions within the founding family are important determinants of payout policy. While family blockholder increase the propensity for a payout to shareholders, outside blockholder have an opposing effect. Finally, we find that common action problems and conflicts among a multitude of family members and/or generations in "real family firms" lead to a higher taste for dividend payments' if compared to firms dominated by the founder ("founder-controlled firms"). Our results prove to be stable against a battery of robustness tests including a matching estimator technique to demonstrate causal effects. Overall, our paper contributes to two strands of literature: the emerging literature on family firms and the more mature literature on corporate payout policy.
Keywords: G32; G35; G30; 330; Family firms; founding family; family ownership; family management; controlling shareholders agency costs; payout policy; dividends; share repurchases; corporate governance